Caracteristicas del consumo de inhaladores en pacientes hospitalizados en el servicio de clinica pediatrica del hospital nacional edgardo rebagliati martins essalud durante el año 2008” - Alva Bocanegra, Ronald Javier (2010)
The aim of this study was to determine the characteristics of the use of inhalers in hospitalized patients in the Department of Pediatric Clinic at Edgardo Rebagliati Martins Hospital in 2008, for which was conducted a descriptive, cross sectional and retrospective study of the drug use. The Information of inhalers consumption in 2008 was obtained from the computerized register. It was used the Anatomical Therapeutic Chemical system (ATC) to designated by codes the drugs to study and get the Defined Daily Doses (DDD) for each of them. Following analysis of the data was obtained that the prevalence of inhaler use was 51.2%. the use of inhalers for treatment group was 71.22% for bronchodilators and 28.78% for corticosteroids. It was proved that there is an increased consumption of inhalers by males (52.69%), compared to the consumption of inhalers by women (47.31%). On the other hand it was noticed that the population of 0-5 years representing the group with higher consumption of inhalers (70.39%), while boys are 5-9 and have 10 to more than 15.32% and 14.39% respectively. It was found that the main indication for inhalers use is not specify Asthma the use of inhalers expressed in DDD/100 day-beds was 74.8 DDD/100beds-day for Salbutamol 100mcg., 46.57 DDD/100 beds day for Ipratropium Bromide 20 mcg., 4.39 DDD/100beds-day for Beclomethasone 250 mcg., 6.06 DDD/100 beds day for Beclomethasone 50 mcg. and 12.19 DDD/100beds day for Fluticasone 50mcg. Finally it was determined that annual spending for inhalers use in hospitalized patients in the Department of Pediatric Clinic was 13 267.50 new soles